DAMPAK ELECTRIC VEHICLE TERHADAP LINGKUNGAN DAN EKONOMI BERKELANJUTAN - Muhamad Lucky Souma; Indah Permata Hakim; Rizki, Rifa Naila; Nur Lailatul Fitriani; Mushawir Mushawir (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
The development of electric vehicles (EV) as part of the transformation of the global transportation system offers a strategic solution to support economic sustainability and environmental preservation. This study aims to analyze the impact of EVs on infrastructure and develop sustainable solutions through a qualitative approach with a case study method. The results of the study indicate that EV adoption can significantly reduce greenhouse gas emissions, improve urban air quality, and support energy efficiency. In addition, the development of the EV industry drives economic growth through job creation and utilization of local resources, especially in the context of implementing the Domestic Component Level (TKDN). However, the success of the transition to an electric-based transportation system is highly dependent on the readiness of the charging infrastructure, policy consistency, and public awareness. This study recommends cross-sector collaboration in developing an EV ecosystem, accelerating the downstreaming of the battery industry, and integrating renewable energy transitions to maximize the positive impact of EVs on sustainable development in Indonesia.